solve by substitution method?
not sure how I am doing this. but the answer is wrong.
- TomVLv 71 decade agoFavorite Answer
Shouldn't that first equation be "4x+7y=48"?
IF so, add the two equations to get:
8y = 64
from which y = 8
substituted into the first equation gives
4x + 56 = 48
x = -2
- Charlie DLv 41 decade ago
You can work out what x = from the first equation
4x + 7 = 48
4x = 41
x = 41/7
Now it substitute it into the second one instead of x:
-4x + y = 16
y - 4(41/7) = 16
y = 16 + 4(41/7)
y = 39.43 (4sf)
Hmm yeah I think tom may be right that you meant 4x + 7y = 48....fml